Research on 5G co-construction and shared voice service solution - Li Xiao; Li Zhijun; Zhou Yuetian; Zhu Xuetian (Dianzi Jishu Yingyong, 2020)
Co-construction and sharing has become a key measure to improve the quality and reduce the cost of 5G mobile network, while the demand of traditional voice service is the basic business of 5G network construction.In this paper, the voice service solutions under different 5G networking modes are discussed, and the VoLTE voice service capability under the shared networking mode of 5G NSA access network is deeply studied. Two technical solutions, VoLTE being carried in the 4G shared anchor point plot of the contractor or in the belonging 4G plot, are proposed.